Benthic responses to organic enrichment under a mussel (Mytilus edulis) farm - Lavoie, Marie-France; Lacoste, Élise; Weise, Andrea M.; McKindsey, Christopher W. (Frontiers in Marine Science, 2024)
Bivalve culture is know to affect some interactions between the water column and the benthic environment with the organic enrichment. An in situ mesocosms experiment was used to determine the influence of mussel biodeposition on the benthic ecosystem in St. Peters Bay, Prince Edward Island, eastern Canada. Eight mussel densities (0 to 2266 mussels m-2) were placed above mesocosms to reproduce the organic enrichment from a mussel farm over 12 weeks. The experimental procedure created an accumulation of organic matter on the seafloor with increasing mussel densities. Some benthic parameters had the predicted response to organic enrichment, with the presence of anoxic sediment in sediment profile images, increased water and organic matter content, and reduced infaunal abundance and species richness. Other parameters, including redox potential, total free sulfides, and the response of the biotic index AMBI, had inconsistent responses to mussel biodeposition-related organic enrichment. Given that other studies done in other locations have observed varying results, results suggest that measurement of various parameters is important to interpret the influence of deposition from mussel farms. The conditions of the site and the study duration are also parameters to consider when evaluating the results from mesocosm studies. Results from this study also suggest that St. Peters Bay is likely impacted by biodeposition from the mussels farmed there.